Regards croisés sur l‘Afrique à l‘ère des (r)évolutions - Caillé, Patricia; Boni, Assié; Pascaline Esoko Bekombe, Marie; Macaire Eyenga, Georges; Nadège Tsogo, Marie; Fofana, Issa; Touré, Fousseyni; Afiwavi Kponvi, Georgette; Serghini, Jaouad; Bouzine, Maria; Mounpe Chare, Idrissou; Fendler, Ute (Akademische Verlagsgemeinschaft München (AVM), 2026)
Renewal, a concept often associated with change and transformation, is considered a special moment of breaking with an obsolete old order, leading to the establishment of a new order that revokes a gloomy past. Indeed, following the fall of the Berlin Wall and French President François Mitterrand's speech in La Baule, several African states, willingly or unwillingly, opted for parliamentary democracy, resulting in the institutionalization of elections as a means of accessing state power. Despite this constitutional progress, political change remains rare in Africa, particularly in French-speaking states. Regimes have remained semi-authoritarian, destroying any possibility of change. As a result, the adoption of democracy has not enabled many socio-professional groups to escape from precariousness. Thus, two decades later, starting in 2010, several African countries have seen the emergence of protest movements, marking the beginning of an era of (r)evolutions. This book brings together case studies that reflect the great diversity of socio-political movements in several countries, such as Burkina Faso, Congo, Côte d'Ivoire, and Morocco, based on various cultural manifestations such as cinema, literature, cultural and religious practices, and media formats in complex political contexts.